2019
DOI: 10.1021/acs.orglett.9b00618
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Biosynthesis of Atrovimycin, an Antitubercular and Antifungal Cyclodepsipeptide Featuring Vicinal-dihydroxylated Cinnamic Acyl Chain

Abstract: Atrovimycin (1), a cyclodepsipeptide containing a unique vicinal-hydroxylated cinnamic acyl chain, was isolated and elucidated from Streptomyces atrovirens LQ13. The biosynthetic pathway of 1 was achieved, revealing cytochrome P450 (Avm43) and epoxide hydrolase (Avm29) enzymes constructing the vicinal-dihydroxy substitution, as well as a tailoring P450 (Avm28) enzyme catalyzing β-hydroxylation of the l-Phe moiety. Atrovimycin shows in vitro antifungal activity and antitubercular activity against Mycobacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(86 citation statements)
references
References 32 publications
2
84
0
Order By: Relevance
“…(Figures 1 A, S1). Notably, CL containing compounds display a broad range of physiological activities, including but not limited to antiangiogenic, [7] antitumor, [5] antibacterial, [1] antifungal, [8] antituberculosis, [9, 10] and enzyme inhibitor [11, 12] . For example, atratumycin displays potent antituberculosis activity, [10] skyllamycin A is a potent inhibitor of the platelet‐derived growth factor (PDGF) signaling pathway, [6] and serpentemycin A possesses a strong inhibitory activity against glycosyltransferase [11]…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…(Figures 1 A, S1). Notably, CL containing compounds display a broad range of physiological activities, including but not limited to antiangiogenic, [7] antitumor, [5] antibacterial, [1] antifungal, [8] antituberculosis, [9, 10] and enzyme inhibitor [11, 12] . For example, atratumycin displays potent antituberculosis activity, [10] skyllamycin A is a potent inhibitor of the platelet‐derived growth factor (PDGF) signaling pathway, [6] and serpentemycin A possesses a strong inhibitory activity against glycosyltransferase [11]…”
Section: Figurementioning
confidence: 99%
“…The CL moiety was proposed to be assembled by a repeating cycle of condensation, reduction, dehydration, isomerization and then cyclization, to give the required product (Figure 1 B). Identification of the biosynthetic gene clusters (BGCs) of CLs and CCNPs indicated that the CL moiety is possibly derived from a type II polyketide synthase (PKS) system [1, 5, 6, 9, 10, 13, 14] . However, unlike the type II aromatic, [15] highly reducing (HR), [16] and acyl polyene (APE) [17] PKSs, CL PKSs not only harbor acyl carrier protein (ACP), ketosynthase (KS), ketoreductase (KR), and dehydratase (DH) (absent in some cases [9] ) domains, but also an isomerase (ISO).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Cinnamic acid derivatives (CAD) have a century-old history as antitubercular agents [8]. However, this family of compounds was never fully explored for their antimicrobial activity against Mtb, and it was not until a decade ago that some studies were conducted to find novel CAD active against tuberculosis [8][9][10][11][12][13][14][15][16]. Noteworthy, trans-cinnamic acid was found to be bacteriostatic at 200 µg/mL against Mycobacterium smegmatis [9] and was reported to show synergism with some first-line antitubercular agents [9,10,12].…”
Section: Introductionmentioning
confidence: 99%